The Taxonomic and Phylogenetic Affinities of Bunopithecus sericus, a Fossil Hylobatid from the Pleistocene of China - Ortiz, Alejandra; Pilbrow, Varsha; Villamil, Catalina I.; Korsgaard, Jessica G.; Bailey, Shara E.; Harrison, Terry (PLOS ONE, 2015)
Fossil hylobatids are rare, but are known from late Miocene and Pleistocene sites throughout East Asia. The best-known fossil hylobatid from the Pleistocene of China is a left mandibular fragment with M2-3 (AMNH 18534), recovered from a pit deposit near the village of Yanjinggou in Wanzhou District, Chongqing Province. Matthew and Granger described this specimen in 1923 as a new genus and species, Bunopithecus sericus. Establishing the age of Bunopithecus has proved difficult because the Yanjinggou collection represents a mixed fauna of different ages, but it likely comes from early or middle Pleistocene deposits. Although the Bunopithecus specimen has featured prominently in discussions of hylobatid evolution and nomenclature, its systematic status has never been satisfactorily resolved. The present study reexamines the taxonomic and phylogenetic relationships of Bunopithecus by carrying out a detailed comparative morphometric study of its lower molars in relation to a large sample of modern hylobatids. Our results show that differences in M2 and M3 discriminate extant hylobatids fairly well, at least at the generic level, and that AMNH 18534 is not attributable to Hylobates, Nomascus or Symphalangus. Support for a close relationship between Bunopithecus and Hoolock is more equivocal. In most multivariate analyses, Bunopithecus presents a unique morphological pattern that falls outside the range of variation of any hylobatid taxon, although its distance from the cluster represented by extant hoolocks is relatively small. Our results support the generic distinction of Bunopithecus, which most likely represents an extinct crown hylobatid, and one that may possibly represent the sister taxon to Hoolock.